Anti-Gametocyte Antigen Humoral Immunity and Gametocytemia During Treatment of Uncomplicated Falciparum Malaria: A Multi-National Study - O’Flaherty, Katherine; Chan, Jo-Anne; Cutts, Julia C.; Zaloumis, Sophie G.; Ashley, Elizabeth A.; Phyo, Aung Pyae; Drew, Damien R.; Dondorp, Arjen M.; Day, Nicholas P.; Dhorda, Mehul; Fairhurst, Rick M.; Lim, Pharath; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction Understanding the human immune response to Plasmodium falciparum gametocytes and its association with gametocytemia is essential for understanding the transmission of malaria as well as progressing transmission blocking vaccine candidates. Methods In a multi-national clinical efficacy trial of artemisinin therapies (13 sites of varying transmission over South-East Asia and Africa), we measured Immunoglobulin G (IgG) responses to recombinant P. falciparum gametocyte antigens expressed on the gametocyte plasma membrane and leading transmission blocking vaccine candidates Pfs230 (Pfs230c and Pfs230D1M) and Pfs48/45 at enrolment in 1,114 participants with clinical falciparum malaria. Mixed effects linear and logistic regression were used to determine the association between gametocyte measures (gametocytemia and gametocyte density) and antibody outcomes at enrolment. Results Microscopy detectable gametocytemia was observed in 11% (127/1,114) of participants at enrolment, and an additional 9% (95/1,114) over the follow-up period (up to day 42) (total 20% of participants [222/1,114]). IgG levels in response to Pfs230c, Pfs48/45 and Pfs230D1M varied across study sites at enrolment (p < 0.001), as did IgG seroprevalence for anti-Pfs230c and D1M IgG (p < 0.001), but not for anti-Pfs48/45 IgG (p = 0.159). In adjusted analyses, microscopy detectable gametocytemia at enrolment was associated with an increase in the odds of IgG seropositivity to the three gametocyte antigens (Pfs230c OR [95% CI], p: 1.70 [1.10, 2.62], 0.017; Pfs48/45: 1.45 [0.85, 2.46], 0.174; Pfs230D1M: 1.70 [1.03, 2.80], 0.037), as was higher gametocyte density at enrolment (per two-fold change in gametocyte density Pfs230c OR [95% CI], p: 1.09 [1.02, 1.17], 0.008; Pfs48/45: 1.05 [0.98, 1.13], 0.185; Pfs230D1M: 1.07 [0.99, 1.14], 0.071). Conclusion Pfs230 and Pfs48/45 antibodies are naturally immunogenic targets associated with patent gametocytemia and increasing gametocyte density across multiple malaria endemic settings, including regions with emerging artemisinin-resistant P. falciparum.